(untitled) (Journal of Applied Learning and Teaching, 2023)
As the application of Artificial Intelligence (AI) continues to permeate various sectors, the educational landscape is no exception. Several AI in education (AIEd) applications, like chatbots, present an intriguing array of opportunities and challenges. This paper provides an in-depth exploration of the use and role of AI in education and research, focusing on the benefits (the good) and potential pitfalls (the bad and ugly) associated with the deployment of chatbots and other AIEDs. The opportunities explored include personalised learning, facilitation of administrative tasks, enriched research capabilities, and the provision of a platform for collaboration. These advantages are balanced against potential downsides, such as job displacement, misinformation, plagiarism, and the erosion of human connection. Ethical considerations, particularly concerning data privacy, bias reinforcement, and the digital divide, are also examined. Conclusions drawn from this analysis stress the importance of striking a balance between AI capabilities and human elements in education, as well as developing comprehensive ethical frameworks for AI deployment in educational contexts.